Inhibitory effects of aspirin-triggered resolvin D1 on spinal nociceptive processing in rat pain models - Meesawatsom, Pongsatorn; Burston, James; Hathway, Gareth; Bennett, Andrew; Chapman, Victoria (Biomed Central, 2016)
Background: Harnessing the actions of the resolvin pathways has the potential for the treatment of a wide range of conditions associated with overt inflammatory signalling. Aspirin-triggered resolvin D1 (AT-RvD1) has robust analgesic effects in behavioural models of pain; however, the potential underlying spinal neurophysiological mechanisms contributing to these inhibitory effects in vivo are yet to be determined. This study investigated the acute effects of spinal AT-RvD1 on evoked responses of spinal neurones in vivo in a model of acute inflammatory pain and chronic osteoarthritic (OA) pain and the relevance of alterations in spinal gene expression to these neurophysiological effects.